Analysis of The Ratio Catalys Promoters BaO/CaO to Methyl Ester Content and Yield in Biodiesel Using Electrocatalytic Reactor (Universitas Trunojoyo Madura, 2022)
The efficiency of biodiesel production from vegetable oils needs to be developed. The process of transesterification using heterogeneous catalysts has been widely studied to replace the role of homogeneous catalysts. The use of BaO promoters into metal oxides increases the activity of heterogeneous catalysts in transesterification reactions. This study was conducted to provide information about the effect of BaO concentrations that are filtered into calcium oxide (CaO) on the transesterification reaction of tofu pulp oil into methyl ester using electrocatalytic methods. The study was conducted at room temperature with a voltage of 18.5 Volts and a reaction time of 120 minutes. Methanol ratio: tofu oil is used at 10:1 with Tetra Hydro Furan (THF) as a co-solvent. The electrocatalytic process is carried out using graphite electrodes. The research variables are the concentration of BaO promoters used at 2%, 4%, and 8%. The parameter of the test is methyl ester content obtained from the results of transesterification reactions with chromatography gas analysis (GC-MS). In this study, the BaO/CaO catalyst was impregnated by wet method and calcined at 450oC for 180 minutes. From the experiments conducted the highest methyl ester yield was obtained in bao / cao catalyst 2% with a yield of 99.99% and biodiesel yield of 94%.